Decision Making Complexities in the Information Era - Rathi, Dinesh (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This study explores the parameter space and associated decision making complexities in the context of text-mining of email-based data. The findings show the impact of different parameters on clustering and classification. These results would help in developing more robust algorithm so that impact of some parameters on mining results is minimized. Cette étude explore l'espace des paramètres et les complexités connexes du processus décisionnel dans le contexte de l'exploration des textes de données courriel. Les résultats montrent l'impact de divers paramètres du groupage et de la classification et permettraient le développement d'algorithmes plus robustes pour réduire l'impact de certains d'entre eux sur l'exploration de textes.